2016
DOI: 10.1111/micc.12280
|View full text |Cite
|
Sign up to set email alerts
|

Central Sympathetic Modulation Reverses Microvascular Alterations in a Rat Model of High‐Fat Diet‐Induced Metabolic Syndrome

Abstract: Modulation of sympathetic overactivity results in the reversal of microvascular rarefaction in the skeletal muscle and left ventricle and improves metabolic parameters in an experimental model of MS in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…Koletsky et al (2003) also achieved similar results with rilmenidine in SHROB rats, with a reduction in triglycerides and cholesterol (Velliquette et al, 2006;Niu et al, 2011). In another model of metabolic syndrome (high-fat diet-induced A Review of Imidazoline Receptors obesity), clonidine and rilmenidine had similar beneficial blood pressure and metabolic effects that were accompanied by a reversal of microvascular rarefaction in skeletal muscles and in the heart (Nascimento et al, 2016). It is interesting to note that under acute conditions, moxonidine and rilmenidine cause hyperglycemia, but less than that induced by clonidine in the same experimental conditions.…”
Section: Imidazoline Subtype 1 Receptors and In Vivo Effectsmentioning
confidence: 67%
“…Koletsky et al (2003) also achieved similar results with rilmenidine in SHROB rats, with a reduction in triglycerides and cholesterol (Velliquette et al, 2006;Niu et al, 2011). In another model of metabolic syndrome (high-fat diet-induced A Review of Imidazoline Receptors obesity), clonidine and rilmenidine had similar beneficial blood pressure and metabolic effects that were accompanied by a reversal of microvascular rarefaction in skeletal muscles and in the heart (Nascimento et al, 2016). It is interesting to note that under acute conditions, moxonidine and rilmenidine cause hyperglycemia, but less than that induced by clonidine in the same experimental conditions.…”
Section: Imidazoline Subtype 1 Receptors and In Vivo Effectsmentioning
confidence: 67%
“…A fine balance between sympathetic and parasympathetic system very sensitively regulates the diameter of the pupil 22,23 and perhaps the microvasculature. 13,15,16,20 Besides the autonomic system, several regulators of cardiac microvasculature physiology are also reported. 14,19,21,[25][26][27] Nevertheless the autonomic system remains the dominant regulator of microvascular function.…”
Section: Discussionmentioning
confidence: 99%
“…14,19,21,[25][26][27] Nevertheless the autonomic system remains the dominant regulator of microvascular function. 20,28 Addressing the commonality between the regulation of pupil diameter and microvasculature by the autonomic system may be clinically useful as a non-invasive and perhaps sensitive index of predicting microvascular complications such as myocardial infraction. We have previously reported the evidence of such commonality in a primate and canine study cohorts wherein iris to pupil area ratio was demonstrated to be a reliable index of borderline changes in autonomic system activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this complex translational perspective is still necessary for studying the interaction between MetS and CCH inducing neurodegeneration. Although brain microvascular dysfunction has been confirmed in several murine models of MetS, including HFD [60,61], Zucker [62], and SHR rats [63], whether MetS causes cognitive impairment due to a decrease in CBF has not been fully addressed yet [64]. In addition, since protein misfolding is a hallmark of neurodegenerative diseases [65], dissecting the exact role of MetS in association with CCH in protein aggregation represents a relevant challenge in the field.…”
Section: Future Directionsmentioning
confidence: 99%